The Brunn-Minkowski Inequality and A Minkowski Problem for Nonlinear Capacity - Akman, Murat; Gong, Jasun; Hineman, Jay; Lewis, John; Vogel, Andrew (Memoirs of the American Mathematical Society, 2022)
In this article we study two classical potential-theoretic problems in convex geometry. The first problem is an inequality of Brunn-Minkowski type for a nonlinear capacity, In the first part of this article, we prove the Brunn-Minkowski inequality for this capacity: In the second part of this article we study a Minkowski problem for a certain measure associated with a compact convex set